Management Approach Combining Prognostic Screening and Targeted Treatment for Patients with Low Back Pain Compared with Standard Physiotherapy: A Systematic Review & Meta-analysis - Collins Ogbeivor (Journal of Spine Practice)
Introduction: Research evidence suggests that a stratified care management approach is better at improving clinical and economic outcomes for low back pain (LBP) patients compared with usual care in the short term. However, it is unclear if these health and economic benefits are sustainable in the longer term. The aim of this study was, therefore, to determine the effectiveness of stratified care compared with standard physiotherapy for LBP treatment.